Psychosocial constructions about crisis, adversity and recovery - Carrasco Tapias, Nayib (Pensando Psicología, 2010)
This paper presents a reflection from the resilience approach around comprehension of how uncertainty break through our capacities to face adversity and positions taken related to it. Particulary it deals with the importance these conceptions about the unexpected and the implications that such signifiers have within everyday life of people and the strategies to face them. Belief systems and coherence sense are strictly linked to constructions of adversity and crisis recovery. On the other hand, the notion of disruptive as an everyday life managed process is dealt within diverse psychosocial contexts, where communitary and social dynamics operate. Disruptive notion wides perspective about adversity around readings of collective psique and the opportunities regarding its approach.
Keywords: disruptive processes; social resources against adversity; resilience